1999
DOI: 10.1177/000456329903600516
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Neural Cell Adhesion Molecules by Human Pituitary Adenomas

Abstract: SUMMARY. Neural cell adhesion molecules (NCAMs) are found predominantly in neural, muscle and endocrine cells. Recent interest has focused on their potential role in tumorigenesis. We have analysed the expression and secretion of NCAM in a series of 48 human pituitary adenomas. Immunocytochemical analysis of 19 adenomas demonstrated NCAM expression in all tumours with, in each case, diffuse cytoplasmic staining being found with variable membrane accentuation. There were no apparent differences in the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is known that progression to neoplasia involves the ability to adhere and interact with the surrounding cells and extracellular matrix, and loss or adhesion difficulties may be a determinant of epithelial neoplasia ( 36 ). Studies have demonstrated immunohistochemical expression of NCAM in pituitary adenomas, including GH-secreting tumors ( 5 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that progression to neoplasia involves the ability to adhere and interact with the surrounding cells and extracellular matrix, and loss or adhesion difficulties may be a determinant of epithelial neoplasia ( 36 ). Studies have demonstrated immunohistochemical expression of NCAM in pituitary adenomas, including GH-secreting tumors ( 5 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unknown if it is generated from sarcoplasm, or cleaved outside by proteases to mediate cell adhesion, or with other unidentified functions. Studies on N-CAM derived from cancer cells have associated secreted and serum N-CAM to disease activity in humans, suggesting a potential use for diagnosis and prognosis (De Jong et al, 1999;Jaques et al, 1993). In fact, N-CAM belongs to the key members of immunoglobulin-like CAM (Ig-CAM) family involved in cell-cell and cell-extracellular matrix adhesion processes in innate immunity.…”
Section: Neural-cell Adhesion Moleculementioning
confidence: 99%
“…Regarding adenohypophyseal cells, considered neuroendocrine cells expressing neuroendocrine proteins such as synaptophysin, chromogranin A and CD-56 [ 31 ], the existing data from the literature although limited have demonstrated that CD-56 expression does not differ between normal pituitary gland cells and PA cells [ 32 , 33 ]. Furthermore, CD-56 does not seem to be related to either PAs proliferation or its invasiveness [ 32 , 34 , 35 ]. Indeed, in our study CD-56 expression was not significantly correlated with any imaging characteristic of PA (size, extrasellar or cavernous sinus invasion) nor with recurrence.…”
Section: Discussionmentioning
confidence: 99%